2016
DOI: 10.1021/acs.organomet.6b00652
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic Nickel Complexes for the Markovnikov-Selective Hydroboration of Styrenes

Abstract: First-row transition metal catalysis offers a cheaper, more environmentally sustainable alternative to second- and third-row transition metal catalysts. Nickel has shown great promise as a tool for the borylation of unsaturated compounds to yield boronic esters, but Markovnikov-selective hydroborations of simple styrenes have not been well-explored. Herein, we report the synthesis of benzyl boronic esters via nickel-catalyzed hydroboration of styrenes using a heteroleptic N-heterocyclic carbene (NHC)–phosphine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 65 publications
2
44
0
Order By: Relevance
“…[288] In 2018, Cárdenas and co-workers disclosed an iron-catalyzed hydroborylative cyclization of 1,6-enynes with 2,2'-biquinoline (129) as the ligand, allowing the construction of carbo-and heterocycles bearing a homoallylic boryl unit (Scheme 104). [288] In 2018, Cárdenas and co-workers disclosed an iron-catalyzed hydroborylative cyclization of 1,6-enynes with 2,2'-biquinoline (129) as the ligand, allowing the construction of carbo-and heterocycles bearing a homoallylic boryl unit (Scheme 104).…”
Section: Critical Reviewmentioning
confidence: 99%
“…[288] In 2018, Cárdenas and co-workers disclosed an iron-catalyzed hydroborylative cyclization of 1,6-enynes with 2,2'-biquinoline (129) as the ligand, allowing the construction of carbo-and heterocycles bearing a homoallylic boryl unit (Scheme 104). [288] In 2018, Cárdenas and co-workers disclosed an iron-catalyzed hydroborylative cyclization of 1,6-enynes with 2,2'-biquinoline (129) as the ligand, allowing the construction of carbo-and heterocycles bearing a homoallylic boryl unit (Scheme 104).…”
Section: Critical Reviewmentioning
confidence: 99%
“…The vast majority of known nonprecious metal catalysts have been found to promote the hydroboration of terminal alkenes with anti‐Markovnikov selectivity. However, a few catalysts based on earth‐abundant metals were recently shown to promote the unusual Markovnikov alkene hydroboration . Following reports of Cu I catalysts, our group reported the first manganese‐catalyzed hydroboration of terminal alkenes with Markovnikov selectivity in 2016 .…”
Section: Introductionmentioning
confidence: 99%
“…Following reports of Cu I catalysts, our group reported the first manganese‐catalyzed hydroboration of terminal alkenes with Markovnikov selectivity in 2016 . In the same year, nickel and iron complexes with N‐heterocyclic carbene (NHC) ligands were reported to catalyze the Markovnikov hydroboration of a range of aromatic terminal alkenes ,. [10a] Very recently, Lu's group also reported an iron‐catalyzed Markovnikov hydroboration of alkenes using amide‐based tridentate ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, these reactions are either highly anti-Markovnikov selective or give a mixture of both Markovnikov and anti-Markovnikov products. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Huang reported that bipyridyl-phosphine cobalt complexes show high activity in the anti-Markovnikov hydroboration of alkenes. 5 Additionally, Chirik developed bis(imino)pyridine cobalt methyl complexes for the anti-Markovnikov selective hydroboration of alkenes (Scheme 1A).…”
mentioning
confidence: 99%